Exploring digital business models in performing arts through a dynamic capabilities lens - Manninen, Kadja (2024)
This PhD research is situated at the intersection of arts, business, and the digital realm. With a particular focus on the crisis-time practices during the Covid-19 pandemic, the thesis investigates how performing arts enterprises (PAEs) can deploy business models in the digital economy. The Covid-19 pandemic acted as a catalyst of digital transformation in many traditionally live activities-based industries, such as the performing arts sector. As live performance-based business models were made temporarily obsolete, the global health crisis marked a drastic drop in income for the sector, but also accelerated organisational decision-making, the adoption of novel digital technologies, and the development of dynamic capabilities (DCs) (Teece, 2007; Teece et al., 1997) in PAEs, which enabled the experimentation with innovative digital business models. Set within this context, this thesis explores the activities of UK-based PAEs to share insights into their recent digital business model innovations, and to discuss the implications of arts and cultural sectors’ pandemic-time ‘digital pivot’ for the post-pandemic performing arts landscape.